Science, democracy, and the American university : from the Civil War to the Cold War - Jewett, Andrew, 1970- (Cambridge : Cambridge University Press, 2012)
"This book fundamentally reinterprets the rise of the natural and social sciences as sources of political authority in modern America. Andrew Jewett demonstrates the remarkable persistence of a belief that the scientific enterprise carried with it a set of ethical resources capable of grounding a democratic culture - a political function widely assigned to religion. The book traces the shifting formulations of this belief from the creation of the research universities in the Civil War era to the early Cold War, tracking hundreds of leading scholars who challenged technocratic modes of governance rooted in a strictly value-neutral image of science. Many of these figures favored a deliberative model of democracy, defined by a vigorous process of public deliberation rather than rationalized administration or interest-group bargaining. This vision generated surprisingly nuanced portraits of science in the years before the military-industrial complex"--
Machine generated contents note: 1. Introduction: thinking about John Dewey, science, and American politics; Part I. The Scientific Spirit: 2. Founding hopes; 3. Internal divisions; 4. Science and philosophy; Part II. The Scientific Attitude: 5. Scientific citizenship; 6. The biology of culture; 7. The problem of cultural exchange; 8. Making scientific citizens; Part III. Science and Politics: 9. Science and its contexts; 10. The problem of values; 11. Two cultures; 12. Accommodation; 13. Conclusion: science and democracy after the Cold War.
Includes bibliographical references and index.
Keywords: Sociology